Behavior of RC columns and those strengthened with FRP composite under an innovative reversing cyclic eccentric axial loading. (15th August 2021) - Razavi, Mohammad; Mostofinejad, Davood; Eftekhar, Mohammadreza
Highlights: An innovative cyclic test was performed to simulate cyclic loading in two opposite directions. A new apparatus was invented to apply the innovative cyclic test. The effects of cyclic loading investigated on non-strengthened and FRP strengthened columns. All types of specimens exhibited reduced bearing capacity and ductility under cyclic loading. Cyclic loading caused a significant reduction in ductility of strengthened column with longitudinal FRP. Abstract: The fundamental role of columns in structural stability calls for an in-depth understanding of their behavior under different loadings. In this study, an innovative test was designed and the required apparatus was manufactured to apply axial eccentric cyclic loading in two opposite directions as an effort to create more realistic conditions for eccentric axial loading of columns in the structures under cyclic loads. For this purpose, six reinforced concrete (RC) columns were tested. The columns included non-strengthened specimens, those strengthened with longitudinal FRP strips installed using the externally bonded reinforcement on groove (EBROG) technique, and those strengthened with full FRP wraps. All the specimens subjected to axial loading with an eccentricity of 90 mm in both monotonic and reversing cyclic method (the innovative method developed herein) to compare the effects of both cyclic and monotonic loadings. The specimens exhibited reduced bearing capacity and ductility under cyclic loading when compared with those subjected to monotonic. Moreover, the trend of the load-deformation relationship of RC columns and those strengthened with FRP wraps were almost the same under monotonic and cyclic loads, while strengthened specimens with longitudinal FRP exhibited different load-deformation trends. Comparison of the specimens strengthened via the two methods used in this study revealed that using longitudinal FRP sheets via the EBROG technique caused a significant (about 60%) increase in bearing capacity under high eccentric loads through a reduction in ductility. Application of FRP wraps, however, exhibited almost no effect on bearing capacity under the same loads but led to the columns' enhanced ductility.